VISUALIZATION OF VOLCANIC ROCK GEOCHEMICAL DATA AND CLASSIFICATION WITH ARTIFICIAL NEURAL NETWORKS - Lacassie Ju.P.; Del solar Ja.R.; Roser B.; Hervé F. (My University, 2006)
An unsupervised neural network technique, Growing Cell Structures (GCS) was used to visualize geochemical differences between four different island arc volcanic rock types: basalts, andesites, dacites and rhyolites. The output of the method shows the cluster structure of the dataset clearly, and the relevant geochemical patterns and relationships between its variables. The data can be separated into four clusters, each associated with a specific volcanic rock type (basalt, andesite, dacite and rhyolite), according to a unique combination of major element concentrations. Following clustering, performance of the trained GCS network as a classifier of volcanic rock type was tested using two test datasets with major element concentration data for 312 and 496 island arc volcanic rock samples of known volcanic type. Preliminary classification results are promising. In the first test dataset 94% of basalts, 76% of andesites, 83% of dacites and 100% of the rhyolites were classified correctly. Successful classification rates in the second dataset were 100%, 80%, 77%, and 98% respectively. The success of the analysis suggests that neural networks analysis constitutes a useful analytical tool for identification of natural clusters and examination of the relationships between numeric variables in large datasets, and that can be used for automatic classification of new data.
Keywords: NEURAL NETWORKS; GEOCHEMISTRY; VISUAL ANALYSIS; CLASSIFICATION; VOLCANIC ROCKS